PPARs at the crossroads of T cell differentiation and type 1 diabetes - Riaz, Farooq; Wei, Ping; Pan, Fan (Frontiers in Immunology, 2023)
T-cell-mediated autoimmune type 1 diabetes (T1D) is characterized by the immune-mediated destruction of pancreatic β-cells. The increasing prevalence of T1D, predominantly in Asian countries, poses significant challenges to the healthcare system, particularly in countries with struggling economies. This review paper highlights the multifaceted roles of Peroxisome Proliferator-Activated Receptors (PPARs) in the context of T1D, shedding light on their potential as regulators of immune responses and β-cell biology. Recent research has elucidated the intricate interplay between CD4+ T cell subsets, such as Tregs and Th17, in developing autoimmune diseases like T1D. Th17 cells drive inflammation, while Tregs exert immunosuppressive functions, highlighting the delicate balance crucial for immune homeostasis. Immunotherapy has shown promise in reinstating self-tolerance and restricting the destruction of autoimmune responses, but further investigations are required to refine these therapeutic strategies. Intriguingly, PPARs, initially recognized for their role in lipid metabolism, have emerged as potent modulators of inflammation in autoimmune diseases, particularly in T1D. Although evidence suggests that PPARs affect the β-cell function, their influence on T-cell responses and their potential impact on T1D remains largely unexplored. It was noted that PPARα is involved in restricting the transcription of IL17A and enhancing the expression of Foxp3 by minimizing its proteasomal degradation. Thus, antagonizing PPARs may exert beneficial effects in regulating the differentiation of CD4+ T cells and preventing T1D. Therefore, this review advocates for comprehensive investigations to delineate the precise roles of PPARs in T1D pathogenesis, offering innovative therapeutic avenues that target both the immune system and pancreatic function. This review paper seeks to bridge the knowledge gap between PPARs, immune responses, and T1D, providing insights that may revolutionize the treatment landscape for this autoimmune disorder. Moreover, further studies involving PPAR agonists in non-obese diabetic (NOD) mice hold promise for developing novel T1D therapies.